THE EFFECT OF BAIT COLOR ON OCTOPUS CATCHES - Rahmatang Rahmatang; Arham Rumpa; Asia Asia; Paduartama Tandipuang; Rafi Ohorella; Angraeni Angraeni (Universitas Mataram, 2024)
Octopuses have a preference for colors often associated with their natural prey, such as small fish or other marine invertebrates. Bait colors that mimic this natural prey can increase the likelihood of an octopus responding and attacking the bait. Handline fishing is one of the methods used by the fishing community in Pattiro Village to catch octopuses using various bait colors, which allows for further study on the effectiveness of bait color in octopus fishing. This research aims to evaluate the impact of different bait color variations on octopus catch rates using handline fishing, with the goal of supporting the development of octopus fisheries in South Sulawesi. The study utilized an experimental fishing method, conducting octopus fishing operations using a specialized handline with colored bait. Data collection was conducted by observing local fishermen’s octopus fishing activities. Based on the effectiveness of the bait colors used, the total catch for blue bait was approximately 8.706 kg (28%), red bait was 13.980 kg (31%), green bait was 2.790 kg (9%), and brown bait was 5.600 kg (18%). The blue bait had a higher catch rate compared to red, green, and brown bait.